Application of 3-dimensional printing technology combined with guide plates for thoracic spinal tuberculosis. Issue 6 (12th February 2021) - Wang, Yifan; Shi, Shiyuan; Zheng, Qi; Jin, Yanghui; Dai, Yingjie
Abstract: Background: To explore the accuracy and security of 3-dimensional (3D) printing technology combined with guide plates in the preoperative planning of thoracic tuberculosis and the auxiliary placement of pedicle screws during the operation. Methods: Retrospective analysis was performed on the data of 60 cases of thoracic tuberculosis patients treated with 1-stage posterior debridement, bone graft fusion, and pedicle screw internal fixation in the Department of Orthopedics, Zhejiang Chinese Medicine and Western Medicine Integrated Hospital from March 2017 to February 2019. There were 31 males and 29 females; age: 41 to 52 years old, with an average of (46.6 ± 2.0) years old. According to whether 3D printing personalized external guide plates are used or not, they are divided into 2 groups: 30 cases in 3D printing group (observation group), and 30 cases in pedicle screw placement group (control group). A 1:1 solid model of thoracic spinal tuberculosis and personalized pedicle guide plates was created using the 3D printing technology combined with guide plates in the observation group. Stability and accuracy tests were carried out in vitro and in vivo. 30 patients in the control group used conventional nail placement with bare hands. The amount of blood loss, the number of fluoroscopy, the operation time, and the occurrence of adverse reactions related to nail placement were recorded. After the operation, the patients were scanned by computed tomography to observe the screw position and grade the screw position to evaluate the accuracy of the navigation template. All patients were followed up for more than 1 year. Visual Analogue Scale scores, erythrocyte sedimentation rate, and C-reactive protein were evaluated before surgery, 6 months after surgery, and 12 months after surgery. Results: Sixty patients were followed up for 6 to 12 months after surgery. One hundred seventy-five and 177 screws were placed in the 3D printing group and the free-hand placement group, respectively. The rate of screw penetration was only 1.14% in the 3D-printed group (all 3 screws were grade 1) and 6.78% in the free-hand nail placement group (12 screws, 9 screws were grade 1 and 3 screws were grade 2). The difference was statistically significant ( P  = .047). The operation time of the 3D printing group ([137.67 ± 9.39] minutes), the cumulative number of intraoperative fluoroscopy ([4.67 ± 1.03] times), and the amount of intraoperative blood loss ([599.33 ± 83.37] mL) were significantly less than those in the manual nail placement group ([170.00 ± 20.48] minutes, [9.38 ± 1.76] times, [674.6 ± 83.61] mL). The differences were statistically significant ( P  < .05). There was no significant difference in VAS score and Oswestry disability index score between the 2 groups of patients before operation, 3 and 6 months after operation ( P  > .05). Conclusion: The 3D printing technology combined with guide plate is used in thoracic spinal tuberculosis surgery to effectively reduce the amount of bleeding, shorten the operation time, and increase the safety and accuracy of nail placement.